2016
DOI: 10.1556/aalim.2015.0012
|View full text |Cite
|
Sign up to set email alerts
|

Role of labels referring to quality and country of origin in food consumers’ decisions

Abstract: Within a survey made of Hungarian awareness of, attitudes towards, and preferences for food labels and pricing, this study focused on consumers' reactions to quality and country of origin labels. Data were collected with a standard questionnaire, face-to-face interviews (1000 participants) in the respondents' home. It became obvious that consumers were looking for information about quality (rating its importance at 4.04) on packages, but information about origin (3.94) and production (3.89) was also important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…Jelen tanulmány az élelmiszer-választással kapcsolatos attitűdöket vizsgálja, kiterjesztve a tudatosság és a döntéshozás felé, ezzel kiegészítve az utóbbi évtizedben Magyarországon, a témában végzett kutatásokat. 5,6,7,8,9,10,11,12 Cikkünk témakörét a digitális szolgáltatások irányába bővítettük ki és a mobilalkalmazások lehetőségeit vizsgáltuk, mind szakirodalmakban publikált eredmények, mind a saját kutatások alapján. A hálózat egyes útvonalait követve láthatjuk, hogy az élelmiszerek témaköre az attitűdök mellett jelentős kapcsolatban áll különböző digitális megoldásokkal, magában foglalva az internetet, a mobil alkalmazásokat és a napjainkban kiemelkedő m-Health (azaz "mobil egészség", vagyis olyan orvosi és közegészségügyi gyakorlat, amely mobil eszközökpéldául mobiltelefonok, betegfigyelő eszközök, digitális személyi asszisztens (PDA), tablet és más vezeték nélküli eszközök -támogatásával valósul meg) témakörét.…”
Section: Bevezetésunclassified
“…Jelen tanulmány az élelmiszer-választással kapcsolatos attitűdöket vizsgálja, kiterjesztve a tudatosság és a döntéshozás felé, ezzel kiegészítve az utóbbi évtizedben Magyarországon, a témában végzett kutatásokat. 5,6,7,8,9,10,11,12 Cikkünk témakörét a digitális szolgáltatások irányába bővítettük ki és a mobilalkalmazások lehetőségeit vizsgáltuk, mind szakirodalmakban publikált eredmények, mind a saját kutatások alapján. A hálózat egyes útvonalait követve láthatjuk, hogy az élelmiszerek témaköre az attitűdök mellett jelentős kapcsolatban áll különböző digitális megoldásokkal, magában foglalva az internetet, a mobil alkalmazásokat és a napjainkban kiemelkedő m-Health (azaz "mobil egészség", vagyis olyan orvosi és közegészségügyi gyakorlat, amely mobil eszközökpéldául mobiltelefonok, betegfigyelő eszközök, digitális személyi asszisztens (PDA), tablet és más vezeték nélküli eszközök -támogatásával valósul meg) témakörét.…”
Section: Bevezetésunclassified
“…In Hungary, there is growing interest and increasing consumer demand for high-quality and healthy local products [ 3 , 4 ]. The intensification of local food products’ production would contribute improving ecosystems and would help towards improving the economic situations of farmers, who form the basis of local development, and are directly related to the achievement of United Nations’ second, 12th, and 15th sustainable development goals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its results indicated that consumers primarily look for information on quality (4.04) on the package of foodstuffs, but they also considered information on origin (3.94) and on production (3.89) important. However, the spontaneous knowledge of indications of origin and quality presented unfavourable results, because 35.5% of the respondents could not name any of them (Szakály et al , 2014).…”
Section: Introductionmentioning
confidence: 99%